2008
DOI: 10.2174/1874609810801030169
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticulated Quercetin in Combating Age Related Cerebral Oxidative Injury

Abstract: Reactive oxygen species e.g. O(2)(*-), H(2)O(2) and *OH generated by the induction of oxidative stress exert a potential threat on the activity of endogenous antioxidant enzymes and substantially influence the aging process and age-dependant neuropathology. Chemical antioxidant is almost ineffective in protecting neuronal cells from oxidative damage as Blood Brain Barrier exists in between blood and brain interstitial fluid that restricts undegradable influx from the circulation into cerebral region. Quercetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 32 publications
0
27
0
2
Order By: Relevance
“…Initially, Das and coworkers 29,97 proposed the use of LPs encapsulating quercetin, administered i.v. to rats (pre-treated with arsenic) as a good formulation to attenuate the oxidative damage induced by ischemia reperfusion injury in the rat brain.…”
Section: Lysosomal Storage Disordersmentioning
confidence: 99%
“…Initially, Das and coworkers 29,97 proposed the use of LPs encapsulating quercetin, administered i.v. to rats (pre-treated with arsenic) as a good formulation to attenuate the oxidative damage induced by ischemia reperfusion injury in the rat brain.…”
Section: Lysosomal Storage Disordersmentioning
confidence: 99%
“…It can scavenge reactive oxygen species, and down-regulate lipid peroxidation due to its ion chelating and iron stabilizing effect [1]. Furthermore it can promote the oxidation of Fe 2+ to Fe 3+ , which is less effective in generating free radicals.…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin has been shown to have anti-inflammatory, anti-blood coagulation, anti-ischemic [9][10][11]. Neuroprotective effects have been demonstrated in a variety of brain injury models including ischemia/reperfusion showing improvement of morphological and functional outcomes [12][13][14][15]. Recently Lee et al [16] have investigated and reported the efficacy of Quercetin on cerebral ischemia/reperfusion injury.…”
Section: Introductionmentioning
confidence: 99%